Un divan à Delhi Psychothérapie et individualisme dans l'Inde contemporaine - Gagnant de Weck, Anne (De l'Orient à l'Occident, 2023)
Since the liberal turn of the 1990s, psychotherapies have been booming in Indian society. This book, devoted to the particular case of psychoanalysis in Delhi, describes how this new practice is becoming part of of new lifestyles. Why is therapy becoming an increasingly common practice? What need does it meet? How does the social structure of the Indian world influence therapy and what are the particularities of Indian-style therapy, compared to its other variations (European or North American in particular)? Based on a rich ethnography and many case studies, Anne Gagnant de Weck shows how the contemporary experience of therapy reflects the tensions caused by the highly contested progression of individualistic values (of autonomy, choice and personal happiness) in a caste society reputed to sanctify the group and deny any value to the individual. By articulating a question about the meaning of therapy in individual lives with a question about the form of its device, the author offers a rich and nuanced description, through the prism of intimacy, of the mental universe of the "new middle class" in India and allows us to advance our own knowledge of psychoanalysis.